2019
DOI: 10.3390/molecules24081585
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Chemical Constituents and Bioactivities of the Extracts from Fruits, Leaves and Root Barks of Lycium barbarum

Abstract: The fruits, leaves and root barks of L. barbarum plant are widely used as functional foods and as ingredients in traditional Chinese prescriptions and patent medicines. They are considered to have different pharmacological activities and health benefits because of their diverse constituents. Here, the chemical constituents of the extracts from fruits, leaves and root barks of L. barbarum were compared by ultra-high performance liquid chromatography coupled with high resolution mass spectrometry (UPLC-HR-MS). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 59 publications
1
36
1
Order By: Relevance
“…In this study we also showed that the level of rutin was increased after gall induction. Our data have slight differences from a recent report which showed that the rutin content in fruits is lower than that in leaves of L. barbarum [18]. This inconsistency might be caused by the difference in the Goji cultivar analyzed.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In this study we also showed that the level of rutin was increased after gall induction. Our data have slight differences from a recent report which showed that the rutin content in fruits is lower than that in leaves of L. barbarum [18]. This inconsistency might be caused by the difference in the Goji cultivar analyzed.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, we compared the galled and ungalled leaves of L. chinense and showed that the average level of chlorogenic acid was increased after gall induction. Both our report and previous reports have demonstrated higher chlorogenic acid content in leaves than in Goji berry [18], as seen in Table 1 of the present study. According to our research, galled Goji leaves have potential in contributing more of the protective effects against oxidative stress, inflammation, and other hepatoand cardio-related syndromes [37,38].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…For example, LC–MS is utilized for the determination of toosendanin in Toosendan Fructus and Meliae Cortex in ChP. Xiao et al used UHPLC–MS to identify 131 compounds and quantify seven of them in the fruits, leaves and root barks of Lycium barbarum [ 51 ]. Zeng et al employed UHPLC-triple quadrupole-MS/MS to determine 20 major constituents including salvianolic acids, tanshinones, flavonoids and triterpenes in different parts of Salvia miltiorrhiza [ 52 ].…”
Section: Advanced Analytical Techniques For Quality Standard Of Tcmmentioning
confidence: 99%